1,3,4-Thiadiazoles as potential EP additives - a tribological evaluation using a four-ball test - Bhattacharya A.; Singh T.; Verma V.K.; Prasad N. (My University, 2025)
This paper reports a comparative study of the wear-reducing efficiency and extreme pressure properties of 0.5% ( w v) admixtures of paraffin oil and 2-amino-5-arylamino-1,3,4-thiadiazole additives and a commercial sulphur-phosphorus additive in a four-ball test. 2-Amino-5-p-Cl-phenylamino-1,3,4-thiadiazole additive shows excellent EP properties as is evident from the surface smoothness of SEM micrographs. The tribochemistry of the wear-scar surface has been investigated by the auger electron spectroscopy (AES) technique. © 1995.